O TEMA ÁGUA E SUA INSERÇÃO NOS LIVROS DIDÁTICOS DE CIÊNCIAS DO ENSINO FUNDAMENTAL - Natália Teixeira Ananias Freitas; Fátima Aparecida Dias Gomes Marin (Universidade do Oeste Paulista, 2016)
This article presents part of the data obtained in the investigation "Environmental and Water Education: educational conceptions and practices in municipal schools", linked to FCT / UNESP. We investigated how the theme water attending the Special Projects of Schools; in the syllabus; in textbooks of Sciences and Geography adopted by the municipality and how is approached by teachers, from its theoretical and methodological conceptions. Through a cut, we present the discussions that are related to Science textbooks. The research is characterized by qualitative approach and case study as of 86/2010 CEP protocol. The investigation has concluded that the water theme is treated superficially and fragmented in Textbook of Sciences manner, requiring that students and teachers use other supplementary materials to approach the subject in the classroom.